Variability of surface circulation and biological productivity of Southern Indian Ocean in remote sensing perspective [electronic resource] - Shenbakavalli Ranjan, 1989-, author 602611; Benny Nettumkara Peter, supervisor 642333; Mohd. Razali Mahmud, supervisor 642331; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Kejuruteraan Geomatik)) - Universiti Teknologi Malaysia, 2016